Modeling of picosecond laser-induced plasma amplification inside a microhole and an implied novel technology to drill microholes with varying diameters with depth. (January 2016) - Dabir-Moghaddam, Navid; Tao, Sha; Wu, Benxin; Shin, Yung C.
Abstract: Microholes with varying diameters at different depths are very desirable in various important applications. However, it is very challenging to produce microholes with varying diameters when the variation is in a complicated way and/or when the hole diameter is very small. This paper presents physics-based modeling work on the interactions among a picosecond (ps) laser pulse, a pre-existing plasma plume inside a microhole, and the hole sidewall. The modeling work implies the potential feasibility of a novel dual-pulse laser ablation and plasma amplification (LAPA) process for drilling microholes with varying diameters at different depths.